2009
DOI: 10.1115/1.2982139
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Characterization of a Conical Swirler Flow Field Under Strong Forcing

Abstract: In this study, a spatiotemporal characterization of forced and unforced flows of a conical swirler is performed based on particle image velocimetry (PIV) and laser Doppler anemometry (LDA). The measurements are performed at a Reynolds number of 33,000 and a swirl number of 0.71. Axisymmetric forcing is applied to approximate the effects of thermoacoustic instabilities on the flow field at the burner inlet and outlet. The actuation frequencies are set at the natural flow frequency (Strouhal number Stf≈0.92) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 24 publications
1
36
1
Order By: Relevance
“…It is known that acoustic instabilities coupled by longitudinal modes change the dynamics of the swirling flow and that a longitudinal acoustic forcing of a rotating cold stream reduces the PVC strength, as demonstrated by Lacarelle et al (2009), but the PVC does not completely vanish in these circumstances, as confirmed numerically by Iudiciani & Duwig (2011). Some recent experiments Vorticity wave: one mode of oscillation supported by the Euler equations; the vorticity mode is convected by the flow and features velocity disturbances in a direction perpendicular to that of the flow Combustion instability: broad range of processes giving rise to oscillations in heat release and resonant coupling between combustion and acoustics and resulting in sound emission, structural vibrations, intensified heat fluxes to the walls, and in extreme cases failure of the system have revealed nonlinear interactions between acoustic instabilities and the PVC , Steinberg et al 2010, confirming that the PVC can be suppressed at highacoustic oscillation amplitudes and that, at intermediate acoustic levels, the velocity signal exhibits three components associated with the PVC: the external forcing and the difference in frequency of the previous two.…”
Section: Large Eddy Simulation In Swirling Flame Dynamicsmentioning
confidence: 97%
“…It is known that acoustic instabilities coupled by longitudinal modes change the dynamics of the swirling flow and that a longitudinal acoustic forcing of a rotating cold stream reduces the PVC strength, as demonstrated by Lacarelle et al (2009), but the PVC does not completely vanish in these circumstances, as confirmed numerically by Iudiciani & Duwig (2011). Some recent experiments Vorticity wave: one mode of oscillation supported by the Euler equations; the vorticity mode is convected by the flow and features velocity disturbances in a direction perpendicular to that of the flow Combustion instability: broad range of processes giving rise to oscillations in heat release and resonant coupling between combustion and acoustics and resulting in sound emission, structural vibrations, intensified heat fluxes to the walls, and in extreme cases failure of the system have revealed nonlinear interactions between acoustic instabilities and the PVC , Steinberg et al 2010, confirming that the PVC can be suppressed at highacoustic oscillation amplitudes and that, at intermediate acoustic levels, the velocity signal exhibits three components associated with the PVC: the external forcing and the difference in frequency of the previous two.…”
Section: Large Eddy Simulation In Swirling Flame Dynamicsmentioning
confidence: 97%
“…It is also appropriate to note here that small flap actuators can also be efficiently used to control vortex formation and mixing in a nonswirling jet (Suzuki et al, 2004) and weakly swirling jet (Saiki et al, 2011). The literature contains a number of studies on dynamics of a premixed flame under periodic forcing (Ayoola et al, 2009;Balachandran et al, 2005;Bellows et al, 2006Bellows et al, , 2007Giauque et al, 2005;Kang et al, 2007;Kim and Hochgreb, 2011;Kim et al, 2010;Kulsheimer and Buchner, 2002;Lacarelle et al, 2009;Palies et al, 2010Palies et al, , 2011Paschereit et al, 1999;Thumuluru and Lieuwen, 2009, among others). In general, the flame response appears to be linear only for small amplitudes of perturbations and manifests a complex reaction to a strong forcing.…”
Section: Introductionmentioning
confidence: 96%
“…The largest error in the determination of the TKE production is due to the computation of the time mean velocity gradient while the statistical error in the computation of the Reynolds shear stress per POD mode is very small since the database is constituted by 9000 data and, in the worst condition, at least 90 wake passing periods have been surveyed with 100 snapshots per period. Typically, POD reaches a statistical convergence at the first 10 modes for more than 200 data (e.g., see Lacarelle et al [25]). …”
Section: Discussionmentioning
confidence: 99%